Variability in vibration input power from the structure-borne sound sorce on plate and beam structures - Saari, Noor Fariza (2015)
Structure-borne source which transmits vibration power to the supporting structure especially in buildings plays a major role in contributing structure-borne noise. The structureborne sources are also capable of causing damage to the receiver structures. In order to prevent noise radiation and structural failure, it is important to characterise the structureborne sound source and to recognize its potential input power. However, the knowledge of the force excitation behaviors from the structure-borne source which creates variability in the input power is still lacking. To give an effective insight of the structural mechanism excited by the structure-borne source, some uncertainties such as the amplitude, excitation phase and location of the excitation force which create the variability in the input power are modelled in this study. Quantification of the uncertainties of the maximum-minimum bands, frequency-averaged mean and variance are obtained from the variability of input power in the infinite and finite structures. It is shown that the variability of the input power reduces as the frequency increases. It is also found that the quantifications of the variability from the finite structure can also be approached using the infinite structure. For characterisation of the structure-borne sound source, thin and thick reception structures are used for the velocity source and the force source assumptions in the reception plate test. It is shown that, the reception plate for the force source assumption, the averaging spatial response across the plate area having low modal density is found to be problematic due to high variability of the plate velocity. Therefore, to obtain a more representative spatially averaged mean-squared velocity, only response points closed to the contact points are taken into account in the calculation. The results show that the measured source mobility from the reception plate is improved. Characterisation using a beam structure is also found feasible in the ’reception structure technique’.